2018
DOI: 10.25225/fozo.v67.i1.a2.2018
|View full text |Cite
|
Sign up to set email alerts
|

Habitat, diet, feeding and resting behaviour of the Korean endemic cobitidIksookimia hugowolfeldi(Cobitidae, Pisces) in the wild

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Similarly, Ibarra-Zatarain & Duncan (2015) reported that gilthead seabream tended to swim slowly either alone or in small groups around the tank during early morning (08:30 hours). Likewise, Park et al . (2018) reported the same resting behaviour in the Korean endemic cobitid ( Iksookimia hugowolfeldi ) in the wild.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Similarly, Ibarra-Zatarain & Duncan (2015) reported that gilthead seabream tended to swim slowly either alone or in small groups around the tank during early morning (08:30 hours). Likewise, Park et al . (2018) reported the same resting behaviour in the Korean endemic cobitid ( Iksookimia hugowolfeldi ) in the wild.…”
Section: Discussionmentioning
confidence: 80%
“…Similar results have been found by Anders et al . (2017) and Park et al . (2018) in cod ( Gadus morhua ) and the Korean endemic cobitid, suggesting that this preference to feed is associated with their natural feeding habits.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The tubular nostril typically appears in bottom-dwelling teleosts is a functional boundary layer between inflow of chemical odors to the olfactory organ (Belanger, 2003;Sarkar et al, 2014;Kim and Park, 2020). Such an olfactory entrance may be related to the benthic habitat of Korean spined loaches, which spends their lifetime on the river bottom (Kim and Park, 2002;Park et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…koreensis, Kim (1975); Iksookimia pumila, Kim and Lee (1987); Iksookimia pacifica, Kim et al (1999); Iksookimia longicorpus, Kim et al (1976); Iksookimia hugowolfeldi, Nalbant (1993); Iksookimia yongdokensis, Kim and Park (1997), based on habitat preference and morphology (Ko, 2015;Park et al, 2016;Ko et al, 2020).…”
Section: O N L I N E F I R S T a R T I C L Ementioning
confidence: 99%